Strategi Penanganan Stunting di Kota Bandung - Wiedy Yang Essa; Nurfindarti, Erti; Nugrahana Fitria Ruhyana (Research and Development Agency Ministry of Home Affairs, 2021)
Despite being one of the metropolitan cities in Indonesia, the prevalence of stunting in Bandung City is more than the World Health Organization (WHO) standard. Stunting is a threat to the quality of human development, also lowering economic productivity. A strategy to reduce and handle stunting is needed so that social and environmental aspects are essential to facilitate the policymaker. This study analyzes the stunting situation in Bandung City and then arranges villages based on the stunting risk index to get an operative recommendation. The quantitative method analysis uses climate change adaptation which includes hazard and vulnerability indicators. At the same time, Focus Group Discussion (FGD) forms the qualitative method with key persons to identify problems and formulate impressive strategies. The results showed that 14 villages have the highest risk of stunting in Bandung City, to be intervention priority. These villages have relatively high poverty, poor access to sanitation, and low adaptive capacity. Recommendations from this study are focused on regional development planning, increasing community participation, and multi-stakeholder cooperation through strengthening innovation, collaboration, and innovation.